Families and the Care of Dependent Older People: Between Reciprocity and Ambivalence - Rodríguez Rodríguez, Concha (Cuadernos de Trabajo Social, 2013)
The care of dependent older people in our social context depends primarily on families. Within this reality, different elements that account for the complexity of the situation are articulated; issues such as social representations on ageing and dependence, self-care and the construction of gender roles, family solidarity, and public accountability for care. This is all articulated with the relational processes that each caregiver family must confront and resolve in order to address the care of dependent persons. The experience of group work with caregivers serves as a guide to show part of these processes and the family dynamics relative to care (the redefinition of bonds, the ambivalence between the duty of providing care and the aspirations, resources, and opportunities available, disorientation, uncertainty, etc). This formalisation does not reflect the complexity of the phenomenon of providing care, however, experiences of the type developed in this article inform about intervention opportunities in areas of primary care, as a resource of complementary support and recognition, in the face of the scarce institutional support that caregivers currently receive.
Keywords: dependence; caregivers; family relationships; support groups